The Effect of Denture Cleansing Solutions on the Retention of Yellow Hader Clips: An In Vitro Study - Reena M. Varghese, DMD, MSEd, MS;1 Radi Masri, BDS, MS, PhD;2 (Journal of Prosthodontics, 2007)
To evaluate the retention of yellow Hader clips after exposure to various denture cleansers.